2013 IEEE 78th Vehicular Technology Conference (VTC Fall) 2013
DOI: 10.1109/vtcfall.2013.6692209
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Packing for Interference Alignment-Based Cognitive Dual Satellite Systems

Abstract: Abstract-Interference Alignment (IA) has been considered a promising technique for spectral coexistence of different wireless systems in an underlay cognitive mode. Furthermore, Frequency Packing (FP) can be considered as an important technique for enhancing the spectrum efficiency in spectrum-limited satellite applications. In this paper, we consider a spectral coexistence scenario of a multibeam satellite and a monobeam satellite with the monobeam satellite as primary and the multibeam satellite as secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
2

Relationship

6
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Moreover, the uncoordinated IA technique protects almost 90 % of the total primary rate and the resource division protects about 65 % of the total primary rate. To enhance the spectrum efficiency further, authors in [13] investigate the effect of the frequency packing in IA based dual satellite cognitive systems and show that the sum-rate increases with the value of frequency packing factor for all the considered IA techniques with the IA coordinated technique perfectly protecting the primary rate for all the considered frequency packing factor (from 0.5 to 1). …”
Section: Multibeam-monobeam Satellite Coexistence In Frequency Domainmentioning
confidence: 99%
“…Moreover, the uncoordinated IA technique protects almost 90 % of the total primary rate and the resource division protects about 65 % of the total primary rate. To enhance the spectrum efficiency further, authors in [13] investigate the effect of the frequency packing in IA based dual satellite cognitive systems and show that the sum-rate increases with the value of frequency packing factor for all the considered IA techniques with the IA coordinated technique perfectly protecting the primary rate for all the considered frequency packing factor (from 0.5 to 1). …”
Section: Multibeam-monobeam Satellite Coexistence In Frequency Domainmentioning
confidence: 99%
“…[3] have shown that a considerable capacity improvement can also be achieved in the four color beam pattern by relaxing the signal orthogonality either in frequency or time domains. This strategy is referred to as Time-Frequency Packing (TFP) (See [2], [9], [7]. Next, from the 3GPP arena, sys-tems based on NOMA have shown they provide a larger spectral efficiency than the schemes based on orthogonal ones [6].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the requirement of finding intelligent (or cognitive) resource allocation, it is important to ensure that the co-existence of multi-satellite systems does not cause interference to other co-channel systems such as FSS systems, mobile satellite services (MSS), or terrestrial systems. In particular, the interference mitigation is more complicated considering a practical dual satellite system (DSS) scenario, in which two satellites (e.g., GSO-NGSO satellites) operate over the same coverage area while sharing the spectrum bands [9]. In the co-existence scenarios of GSO-NGSO networks, in-line interference arises whenever an NGSO satellite passes through a line of sight path between an earth station and a GSO satellite [10].…”
Section: Introductionmentioning
confidence: 99%